Gut Microbiota in Rheumatic Diseases Pathogenic Role and Therapeutic Potential - Kusy, Bartłomiej; Dudziński, Maciej; Różańska, Martyna; Robak, Michał; Bajkacz, Agnieszka; Płonka, Marcin; Michalak, Mateusz (Quality in Sport, 2025)
The gut microbiota plays a crucial role in maintaining the body’s homeostasis, and its imbalance—referred to as dysbiosis—is increasingly associated with the pathogenesis of autoimmune diseases, including rheumatic disorders. In recent years, there has been growing interest in the complex interactions between the gut microbiota and the immune system, which may influence the development and progression of conditions such as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) and Psoriatic arthritis (PsA) The aim of this paper is to analyze the current state of knowledge regarding the relationship between the gut microbiota and rheumatic diseases, with particular emphasis on the immunological mechanisms involved. The work presents examples of alterations in gut microbial composition in patients with selected rheumatic conditions and explores the possible consequences of these changes for immune system function. Furthermore, the paper discusses potential therapeutic strategies aimed at modulating the gut microbiota, including the use of probiotics, prebiotics, dietary interventions, and the innovative approach of fecal microbiota transplantation (FMT). By reviewing available studies, the paper evaluates the efficacy and safety of these methods and outlines directions for future research in the context of microbiota-targeted therapies as supportive treatment options for rheumatic diseases.